Vegan labeling for what is already vegan: Product perceptions and consumption intentions. (1st August 2022) - Stremmel, Gesa; Elshiewy, Ossama; Boztug, Yasemin; Carneiro-Otto, Fernanda
Abstract: Given the increasing popularity of vegan labels, our study examines the effect of vegan labeling on product perceptions and consumption intentions. We focus on randomly-vegan products which are products that have neither undergone any special reformulation to be vegan nor explicitly aim to serve the market segment of vegans and vegetarians. Food marketers are often tempted to add a vegan label to their randomly-vegan products to capitalize on the growing popularity of vegan food. Our results show that labeling randomly-vegan products biases the perceived healthiness, expected taste, and perceived sustainability, but only if consumers do not expect such randomly-vegan products to be vegan by default. This translates into altered consumption intentions for these unexpected-vegan products with a vegan label (vs. no label). Importantly, this applies to both utilitarian and hedonic products. No effects attributed to the vegan label (vs. no label) were found for randomly-vegan products that consumers expected to be vegan by default.